HIF-2α, acting via miR-191, is involved in angiogenesis and metastasis of arsenite-transformed HBE cells. Issue 1 (19th November 2015) - Xu, Wenchao; Luo, Fei; Sun, Baofei; Ye, Hua; Li, Jun; Shi, Le; Liu, Yi; Lu, Xiaolin; Wang, Bairu; Wang, Qingling; Liu, Qizhan; Zhang, Aihua
Abstract : Arsenic is a well established human carcinogen that causes diseases of the lung. Abstract : Arsenic is a well established human carcinogen that causes diseases of the lung. Some studies have suggested that hypoxia-inducible factors (HIFs) and microRNAs (miRNAs) are involved in human lung cancer; however, their molecular mechanisms that causally contribute to arsenite-caused malignant transformation of cells remain unclear. To elucidate the mechanisms of angiogenesis and metastasis of lung cancer caused by arsenite, we investigated the role of HIF-2α regulation of miRNA-191 (miR-191) in the angiogenic and metastatic properties of human bronchial epithelial (HBE) cells transformed by arsenite. In HBE cells, HIF-2α binds to the hypoxia response element (HRE) in the promoter region of miR-191 and initiates transcription of miR-191. Blocking of HIF-2α with siRNA inhibited the up-regulation of miR-191, Wilms' tumor 1 (WT1) protein, matrix metalloproteinase 9 (MMP-9), vascular endothelial growth factor (VEGF), and the down-regulation of brain acid-soluble protein 1 (BASP1). In arsenite-transformed HBE (T-HBE) cells, down-regulation of HIF-2α by siRNA blocked the process of angiogenesis and decreased their neoplastic properties and metastatic capacity, which were reversed by over-expression of miR-191 or by up-regulating WT1. Thus, HIF-2α up-regulates WT1 via miR-191, both of which are involved in the angiogenesis and metastasis of T-HBE cells. The results present a better understanding of the processes involved in lung cancer caused by arsenite exposure.